Solar pv placement and sizing for line stability enhancement and optimal operating cost - Salleh J.M.; Rahmat N.A.; Marzuki N.H.; Otoh O.F. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Nowadays, many countries have started to implement and installed solar photovoltaic (PV). The initial designs of existing power systems were not integrating with any renewable energy (RE) including PV. So, the small scale PV may not have any effect on these power systems. However, integrating large scale PV might raise several power quality issues including power system stability. Power system stability has become major attention where the main focus is on voltage stability.Voltage stability is related on electrical grid capacity to balance the Total Power of Demand (PD) and Total Power generated by Generator (Pgtt). Instability of the voltage can cause inability of the power system to meet the demand of reactive power. The lack of reactive power will cause instability in the power system.This paper present optimal placement and sizing of PV for stability enhancement and operating cost minimization. In this research, reactive power has gradually increased and Fast Voltage Stability Index (FVSI) is applied to analyze voltage stability. PV is applied to stabilize voltage stability of the power system. Economic Load Dispatch (ELD) is conducted to determine the optimal cost and loss. DEIANT is conducted to optimize the total cost and the total loss after solar PV implementation. Simulation result indicates the effectiveness of the proposed technique for stability enhancement and operating cost minimization. BEIESP.